Frequência de Neospora caninum e de Toxoplasma gondii em Cachorro-do-Mato (Cerdocyon thous, Linnaeus, 1776) no estado de Alagoas, Brasil - Pedrosa, Camila de Morais (2018)
Brazil has a great fauna and flora variety. Due to the human intervention this variety has been threatened, though. This intervention has been causing disorders in natural habitats and the evasion of wildlife animals population to urban areas, resulting in interaction among human population and domestic animals, promoting the transmission of infectious diseases common to those animals, for instance neosporosis and toxoplasmosis. Neosporosis and toxoplasmosis are parasitic diseases caused by Neospora caninum and Toxoplasma gondii respectively. Those are protozoans responsible for significant breeding and economical worldwide losses, known as one of the main causes of abortions in ruminants. Nevertheless, Toxoplasma gondii is not only limited to the animal life, it might expand to human populations, being known as one of the most worldwide spread zoonosis. Several researches have shown the occurrence of Neospora caninum and Toxoplasma gondii in wild canids, evincing the importance of these species as intermediate and definitive hosts of this protozoan. In this segment, being the crab-eating fox (Cerdocyon thous), an intermediate host, could be possible to consider this canid a definitive host. Therefore, new researches in this area must be carried out to stablish the relationship between this animal in the cycle of these pathogens and its impact in producing animals and public health.